Understanding factors predicting violent recidivism - Phua, Hong Ling (Nanyang Technological University, 2022)
Recidivism studies had acknowledged the importance of extending one’s understanding beyond general recidivism, given that findings had shown associated factors to differ across specific offence types. While violent offending had been associated with significant negative consequences and high social cost, there was a lack of studies looking at the relationship of associated factors with violent recidivism among local adults. The current study aimed to examine factors predicting violent recidivism among local offenders who were released from custody. As other recidivism studies had suggested potential differences between first time and repeated offenders, the current study splits the analysis to examine the groups separately. A combination of methodologies including logistic regression, dominance analysis, random forest, and generalized estimating equations had been utilized. Results had showed that there were significant similarities and differences between the first timers and the non-first timers. Variable importance plots extracted had also suggested that some variables were more significant than the others. However, the results also proposed that the models lacked the overall efficiency to clearly distinguish between the recidivists and non-recidivists, possibly due to the lack of effective variables to further provide distinctions between the two groups. As the current study had only examined criminal history, demographic variables, and several social proxies, further studies could build on it to include additional dynamic and psychological measures that were also suggested to be key factors in predicting violent recidivism. On top of risk factors, protective factors could also be incorporated for a more holistic understanding of violent recidivism.